Функціональні зв'язки між ефектами води Нафтуся на канальцеву секреторно-транспортну та імунну системи щурів. Повідомлення 2: Канальцева секреція і параметри спленоцитограми та гемолімфоаденоцитограми - Кретчак, Р.І.; Івасівка, С.В.; Попович, І.Л.; Ковбаснюк, М.М.; Гучко, Б.Я.; Білас, В.Р. (Медична гідрологія та реабілітація, 2006)
В рамках концепции об общности механизмов функционирования канальцевой секреторно-транспортной и фагоцитарно-лимфоидной систем выявлены существенные связи между скоростью почечной канальцевой секреции и параметрами фагоцитоза, лейкоцитограммы крови, стеноцитогаммы и гемолимфоаденоцитограммы крыс в условиях курсового напаивания их водой Нафтуся per se и в сочетании с цитостатиком или анаболиком. It is shown that increase of canalicular secretion in rats becaused by drinking of water Naftussya accompanied increase massa of haemolymphatic node and contents in its of endothelio-, reticulo-, lymphocytes, eosinophyles and macrophages, blood level lymphocytes, monocytes and segmental nucleare neutrophyles but decrease activity and completion of phagocytose of neutrophyles and level of lymphoblastes in splenocytogramme. The using of cytostatic drug abolishes but anabolic drug potentiates both activating and inhibiting influence of water Naftussya.